Simulasi Antena Mikrostrip D-Shaped Dengan Pencatuan Microstrip Line Untuk Aplikasi Wireless Body Area Network (WBAN) Pada Frekuensi 2.4 GHZ - Dian Rahmanda; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Microstrip antenna as a communcation device has small dimension with good receiving signal ability, this microstrip antenna is a technology that can be used on a wireless network application with high rate data speeds. Microstrip antenna is very suitable for wireless body area network (WBAN) applications. This microstrip antennas are small, designed in such a way that can be used daily without causing bad image effects for user apperance. WBAN device can be implemented in various fields such as industry, science and medical (ISM). The result of the antenna design is carried out by simulation process using applications. The target results from the antenna are: frequency 2.4 GHz, return loss ≤ -10 dB, dan VSWR ≤ 1.9.Keyword: microstrip antenna, wireless body area network, return loss, VSWR